Reactive power planning for minimization loss and voltage control using genetic algorithm / Uma Baki Mohhamad - Mohhamad, Uma Baki (2007)
Reactive power planning is to maintain node voltage within permissible limits and minimize transmission losses by rescheduling reactive power flow. The optimal reactive power planning can be performed using various optimization technique .